Nutrient content in rice husk ash of some malaysian rice varieties - A. B., Hashim; Hussin, Aminuddin; K. B., Siva (Universiti Putra Malaysia Press, 1996)
Analysis performed on more than 60 samples of 10 different paddy varieties showed 21.33% of the rough rice comprised rice husk, while 13% of the husk constituted rice husk ash. The nutrient content of rice husk ash was 80.26% silica, 0.38% phosphorus, 1.28% potassium, 0.21% magnesium and 0.56% calcium. Statistically, nutrient composition is significantly influenced by varietal differences. As a potential material for fertilizer use, the estimates of total nutrient supplementation available from rice husk ash per annum are discussed.